SWOT ANALYSIS OF MATHEMATICS EDUCATION IN UKRAINE - Khvorostina, Yurii; Yurchenko, Artem (Physical and Mathematical Education, 2025)
Formulation of the problem. In the context of globalization, rapid technological progress, and the challenges posed by Ukraine’s martial law, the issue of the quality of mathematics education is of particular relevance. As a fundamental science, mathematics determines the level of training of specialists in various fields, from engineering and IT to economics and natural sciences. Therefore, analyzing its current state and identifying its strengths and weaknesses, opportunities, and threats is necessary for further improving educational policy. Materials and methods. The SWOT analysis was used. The analysis involved scientific publications, reports of European institutions, and content analysis of Internet resources based on research results and empirical data analysis. Results. The strengths (basic mathematics education, its sustainability, focus on competence-based approaches and international cooperation, STEM) and weaknesses (low international assessment scores, socio-economic inequality, outdated teaching methods, interruptions in education due to war, limited coverage of complex topics, insufficient teacher training), opportunities (integration of digital learning tools, strengthening STEM education, international cooperation, modernization of training of future mathematics teachers and support for working teachers, and development of critical thinking) are characterized. Conclusions. The results show that, despite its considerable potential, the mathematics education system in Ukraine needs systemic changes to overcome structural weaknesses and threats associated with the war and other negative factors. Recommendations include integrating international assessment standards into mathematics curricula, developing specialized educational trajectories as early as secondary school, strengthening the link between mathematics and applied STEM disciplines, finding long-term investments in teaching staff and digital infrastructure, enhancing the financial sustainability of teaching staff, and others.